قرآن مجید پرمستشرقین کےاعتراضات کاتنقیدی جائزہ: تفسیرالشعراوی کا مطالعہ: A critical review of Orientalists' objections on the Holy Qur'an: A Study of Tafsīr al-Shaʻrāwī (Al-Qamar, 2023)
The orientalists studied the history of East, its religious, its beliefs, and its characteristics, especially the Islamic community. The motive of their study was to attack and destroy the Islamic heritage. However, there are many objective orientalists who judged with the superiority of the Islamic religion and the divinity of Holy Quran. But most of them kept on attacking the Quran, Islam and Muslims, which resulted in dubiousness and defamation of the Holy Quran, its sanctity, and its divinity. Muslim scholars have not failed to defend Islam and advocate for its book since the emergence of these orientalists. Sheikh Al-Sharawi was the one who averted their suspicions in this era, exposed many of their misgivings about the Quran and refuted their allegations as he interprets the Holy Book of God. So, this research came out to clarify the responses of Sheikh Al-Sharawi about the Orientalists’ Dubiousness about the Holy Quran confined to what was mentioned in his interpretation of the two surahs of Al- Baqara and Aal Imran. The research consists of an Introduction. The Introduction handles the concept of orientalism in language and terminology, the orientalists and examples of them, as well as explaining some of their suspicious about the Holy Qur'an. The first Division shows the responses of Sheikh Al-Sharawi to the Orientalists’ Dubiousness mentioned in some verses of Surat Al-Baqara, and the second division shows the Sheikh Al-Sharawi's responses to the Orientalists’ Dubiousness mentioned in Surat Aal Imran. The research concluded with important results including: Sheikh Al-Sharawi's proficiency in his strife for defending the Holy Quran and refuting and nullifying the Orientalists’ Dubiousness. Nullifying it is a matter that requires a deep understanding of the Quran as Sheikh Al-Sharawi did.
Keywords: Orientalists; Objections; Holy Qur'an; Tafsīr al-Shaʻrāwī